IDEAL MORAL HADIS MUZA>RA’AH DAN RELEVANSINYA DENGAN RKUHP PIDANA DENDA TERNAK (Studi Analisis Hermeneutika Hadis Fazlur Rahman) - Mushodiq, Muhamad Agus (IAIN Kediri, 2020)
This paper aims to descibe the relevance of the muzara'ah hadith and RKUHP which literally contain conflicting spirits. The author tries to find the rhetoric of traditions through historical search and formulates moral ideals that can be applied and contextualized to the present age. In conducting research, the author uses qualitative-descriptive literature research methods, with material objects of muzara'ah hadith and RKUHP criminal article 278. While the formal objects used are Fazlur RahmanÃ¢â‚¬â„¢s hadith hermeneutics. The results of this study are (1) Fazlu RahmanÃ¢â‚¬â„¢s hadith hermeneutics emphasizes on the fusion of formal traditions, returning to their nature as living sunnah in the community. Melting the Hadith into a Sunnah does not mean practicing it through textual interpretation, it is necessary to have a historical study to find a retio legis (goal) and formulation of a moral ideal, so that the essence of the hadith can be applied and applied in contemporary times, (2) Muzara'ah hadith with RKUHP has a spirit or with the RKUHP the same essence that is motivating farmers to enthusiasm in farming as a retio legis, so that there is no contradiction between the two. (3) Moral ideal that can be applied to the current situation is an effort to strengthen the work ethic of farmers with pro-farmer government policies, both legally through the RKUHP, minimizing food imports or with more concrete policies, namely by providing plant seeds, seeds, fertilizer, and agricultural equipment free of charge for farmers.Keywords:Ã‚Â MuzaraÃ¢â‚¬â„¢ah Hadith, Fazlur RahmanÃ¢â‚¬â„¢s Hadith Hermeneutics, Moral Ideal, Retio Legis